2017
DOI: 10.1007/s13205-017-0788-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacopaside N1 biosynthetic potential of endophytic Aspergillus sp. BmF 16 isolated from Bacopa monnieri

Abstract: Chemically unique environment of endophytes makes them to have various adaptive mechanisms for survival. One of such mechanisms involves the production of pharmacologically significant plant-specific metabolites. In the present study, 26 endophytic fungi were isolated from stem of Bacopa monnieri (L.) Wettst. plants. All the isolates were screened for bacopaside production property by HPLC. Among these, the fungal isolate BmF 16 which was identified as Aspergillus sp. was confirmed for bacopaside N1 production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Saponins [ 34 ] and terpenoids [ 35 ] have multiple therapeutic values and are found usually in medicinal and aromatic plants. It was found that three isolated endophytic fungi were able to produce saponins and terpenoids which are in similar lines to other reports [ 34 , 36 ]. The crude extract of Aspergillus terreus (strain SUBL206) showed the presence of phenolics, tannin, flavonoids, and steroids.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Saponins [ 34 ] and terpenoids [ 35 ] have multiple therapeutic values and are found usually in medicinal and aromatic plants. It was found that three isolated endophytic fungi were able to produce saponins and terpenoids which are in similar lines to other reports [ 34 , 36 ]. The crude extract of Aspergillus terreus (strain SUBL206) showed the presence of phenolics, tannin, flavonoids, and steroids.…”
Section: Resultssupporting
confidence: 89%
“…Among aforesaid strains, SUBL33 produce highest quantity of Bacoside A3 (4093 μg mL −1 ), Jujubogenin isomer of Bacopasaponin C (65,339 μg mL −1 ), and Bacopasaponin C (1325 μg mL −1 ) while Bacopasaponin II was produced maximum by SUBL51 (13,030 μg mL −1 ) (Table 7 ). Although, Jasim et al [ 36 ] have characterized and reported the synthesis of bacoside from Aspergillus spp. under in vitro conditions but it is a novelty of our work which reports both withanolides and bacosides from endophytes including A. terreus in same metabolites in reasonable quantity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in dementia and amnesia, the protein acetylcholinesterase (AChE) is implicated, while α -synuclein is associated with Parkinson's disease. Furthermore, β -amyloid is closely linked to Alzheimer's disease, and VGluT1, VGluT2, and VGluT3 are involved in schizophrenia [12,13]. The glutamate-8 receptor (mGluR8) plays a role in epileptic seizures.…”
Section: Neuroprotective Effects Of Bacopa Monnierimentioning
confidence: 99%
“… - Cytotoxic and antimicrobial activity Jain et al [ 143 ]; Singh et al [ 148 ]; Katoch et al [ 169 ] - - Aspergillus sp. Bacopaside Jasim et al [ 170 ] Ephedra foliata Boiss. ex C.A.…”
Section: Endomicrobial Diversity Of Important Medicinal Plants/genusmentioning
confidence: 99%